Sistem Pendukung Keputusan untuk Penentuan Penerima Bantuan Pendidikan di SMK Negeri 2 Binjai Menggunakan Metode Waspas - Zhya Anggraini; Yani Maulita; Kristina Annatasia Br Sitepu (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Advances in information and communication technology (ICT) have revolutionized various aspects of life, including the education sector. The application of technology in education enables more flexible, interactive, and personalized learning, as well as expanding access for students in various regions, including remote areas. SMK Negeri 2 Binjai is one of the vocational education institutions in Binjai City that is currently facing challenges in the process of determining recipients of educational assistance, particularly the Indonesia Pintar (PIP) Program, which is intended for underprivileged students. Until now, the selection mechanism for PIP recipients has been carried out manually, making it prone to subjectivity, lack of transparency, and limited integrated data. To overcome this problem, a decision support system is needed to help schools determine the recipients of educational assistance objectively and structurally using the Weighted Aggregated Sum Product Assessment (WASPAS) method, which is an effective multi-criteria decision-making technique for processing various assessment criteria to produce the best alternative ranking. The results of the calculation using the WASPAS method produced different preference values (Qi) for each student alternative. The highest score was obtained by Ilyas Ramadhanu with a Qi of 0.6899, followed by Binar Sembiring with a Qi of 0.5963, and Dimas Dwi Andika with a Qi of 0.5790. The lowest value was obtained by Adit Rahmazi with a Qi of 0.3852.